Optimasi Persediaan Komponen AC pada Perusahaan Jasa Pemeliharaan dan Perbaikan AC dengan Metode Just in Time CV Cahaya Berkah Ilahi - Muhammad Roybafih; Indro Kirono (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
CV Cahaya Berkah Ilahi is a company engaged in the maintenance and repair of air conditioners (AC) that has been operating for more than 3 years. With rapid growth, the company faces various challenges, particularly in the suboptimal management of AC component inventory, which impacts operational efficiency and customer satisfaction. This has prompted the company to implement the Just In Time (JIT) method in inventory management, aimed at enhancing the ability to respond to market demand and reduce operational costs. This study aims to analyze the Just-in-Time (JIT) method if applied at CV Cahaya Berkah Ilahi. This descriptive qualitative study uses the AC component raw material inventory at CV Cahaya Berkah Ilahi as the unit of analysis, along with two key informants: the owner and the head technician. The results of the study indicate that the implementation of the Just-in-Time (JIT) method can serve as a strategic solution to reduce inventory costs and improve operational efficiency. However, the success of JIT implementation depends on several factors, including effective communication among team members, strong relationships with suppliers, and the efficient use of information technology.